Who was that woman, anyway? snapshots of a lesbian life - McLeod, Aorewa (Victoria University Press, 2013)
Emerging brittle and cynical from a wildly dysfunctional family, Ngaio careers from ice cream factory to children's home to Oxford to rehab. Along the way, she discovers herself and her sexuality -- at raucous parties with trainee nurses, in feminist encounter groups and Wiccan covens, in university classrooms and legendary sapphic hotspots. This novel delivers vivid and hilarious snapshots of late 20th Century lesbian life: witty, tender, frank.